Demonstration of papilloma virus particles in cervical and vaginal scrape material: a report of 10 cases. Issue 5 (May 1981) - Stanbridge, C M; Mather, J; Curry, A; Butler, E B
Abstract : The finding of virus particles by transmission electron microscopy (TEM) in fixed cervical and vaginal scrape material and their identification as papilloma viruses by negative staining is described. The colposcopic, cytological, and histological appearances in a group of 10 patients in whom virus particles were seen are discussed and the possibly considered of an association between papilloma virus infection and the development of cervical intraepithelial neoplasia (CIN) and multifocal intraepithelial neoplasia of the female lower genital tract.